2011
DOI: 10.1007/s10664-011-9158-8
|View full text |Cite
|
Sign up to set email alerts
|

A practice-driven systematic review of dependency analysis solutions

Abstract: When following architecture-driven strategies to develop large softwareintensive systems, the analysis of the dependencies is not an easy task. In this paper, we report a systematic literature review on dependency analysis solutions. Dependency analysis concerns making dependencies due to interconnections between programs or system components explicit. The review is practice-driven because its research questions, execution, and reporting were influenced by the practice of a group of software architects at Phil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(5 citation statements)
references
References 92 publications
0
5
0
Order By: Relevance
“…Various types of dependencies are distinguished in literature. Callo Arias et al consider that all types fit into three main categories: structural dependencies, behavioral dependencies, and traceability dependencies. The category of structural dependencies, dependencies among parts of a system, is of interest to our study, because static analysis tools focus on dependencies that can be found by inspecting the source code.…”
Section: Dependency Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Various types of dependencies are distinguished in literature. Callo Arias et al consider that all types fit into three main categories: structural dependencies, behavioral dependencies, and traceability dependencies. The category of structural dependencies, dependencies among parts of a system, is of interest to our study, because static analysis tools focus on dependencies that can be found by inspecting the source code.…”
Section: Dependency Analysismentioning
confidence: 99%
“…Callo Arias et al state that dependency analysis approaches that identify structural dependencies have a high degree of accuracy. Our research outcome shows that it is appropriate to be aware of the limitations of the tools used.…”
Section: Related Workmentioning
confidence: 99%
“…Dependency analysis is the method of identifying the dependences of a software program [20]. Callo Arias et al [21] categorizes dependencies to be structural, behavioral, and traceability. Structural dependencies are derived through static analysis of source code.…”
Section: Introductionmentioning
confidence: 99%
“…Dependency analysis is the method of identifying the dependences of a software program [20]. Callo Arias et al [21] categorizes dependencies to be structural, behavioral, and traceability. Structural dependencies are derived through static analysis of source code.…”
Section: Introductionmentioning
confidence: 99%